Problematyka imperium Państwowej Inspekcji Pracy na przykładzie wystąpienia inspektora pracy - Sobol, Michał (Studia Prawa Publicznego, 2021)
The labour inspector’s statement constitutes a non-statutory form of enforcing labour rights. In this context, we can see a variety of problems related both to the impact of the legal measure itself, appealing against it, as well as to the role it plays in ensuring compliance with employment rights. The jurisprudence and literature to date indicates explicitly that the employer’s failure to comply with the content of the labour inspector’s speech does not give rise to any negative legal consequences. Nevertheless, employers who do not agree with the solutions recommended by the authority through the labour inspector’s speech perceive this specific measure as a special type of decision. The decision itself, in turn, seems to be a natural manifestation of the state, the authority indicating to the subject of law the individual directions of its behaviour. However, this is, in fact, a different act. The article doubts the implementation of the model of labour supervision and control assumed by the legislator in the light of the measure outlined in the labour inspector’s speech. As a result, allowing this measure to be left to the inspector’s discretionary use may lead to the reinforcement of the feeling of a lack of efficiency on the part of the state bodies in the field of protection of workers’ rights, especially that the cases of its use are an open catalogue, which includes issues such as working time or the employment of young people. In order to better understand these trends, two examples are discussed where the National Labour Inspectorate had an impact on situations of a gross violation of labour law standards. A de lege ferenda direction has also been indicated, which means the creation of the institution of “re-inspection” of the employer. The existence of a non-authoritative “recommendation”, which is a statement by the labour inspector, is in fact a manifestation of the implementation of Article 17, paragraph 2 of the ILO Convention No. 81, which would not be incompatible with the consequence in the form of addressing a statement.